The Top Management Triangle in Voluntary Hospitals (II) - Gordan, Paul J. (Academy of Management Journal, 1962)
Part II. Focuses on a study about the management of voluntary hospitals. Discussion on hospital administration; Comparison on the goals and objectives of profit and non-profit organizations; Relationship of administrators and medical personnel.